Emotion dysregulation and dissociation contribute to decreased heart rate variability to an acute psychosocial stressor in trauma-exposed Black women. (October 2021) - Powers, Abigail; Mekawi, Yara; Fickenwirth, Maximilian; Nugent, Nicole R.; Dixon, H. Drew; Minton, Sean; Kim, Ye Ji; Gluck, Rachel; Carter, Sierra; Fani, Negar; Schwartz, Ann C.; Bradley, Bekh; et al.
Abstract: Reduced heart rate variability (HRV) in response to stress is a biomarker of emotion dysregulation (ED) and is related to posttraumatic stress disorder (PTSD), yet less is known about its role with dissociation in trauma-exposed adults. The goals of the current study were to examine unique patterns of associations between ED, dissociation, and PTSD with HRV at 15, 30, and 45 min (T1, T2, T3) following an acute psychosocial stressor task in a sample of 49 trauma-exposed, urban-dwelling Black women. Associations with baseline psychophysiology measures were also examined. ED and dissociation were assessed using self-report; PTSD was determined using a semi-structured interview. Heart rate (HR) and HRV, indexed with low frequency/high frequency (LF/HF) ratio and respiratory sinus arrhythmia (RSA), were measured with electrocardiogram recordings. ED and dissociation were positively correlated with LF/HF ratio at T3 ( p < .05). There were no significant differences between individuals with PTSD versus those without PTSD in HR or HRV following acute stressor; PTSD diagnosis was related to higher HR at baseline. Latent growth modeling revealed that ED was associated with higher LF/HF ratio directly following acute stressor, while dissociation was associated with increase in LF/HF ratio over time. These findings demonstrate that ED is related to higher sympathetic reactivity for a prolonged period of time following stress exposure, while dissociation shows a delayed association with LF/HF ratio, suggesting a distinct impaired parasympathetic activation pattern exists for dissociation. Highlights: Trauma impacts physiological function and response to stress. Psychophysiological response to stress was measured in trauma-exposed Black women. Emotion dysregulation was related to sustained sympathetic response to stress. Dissociation was related to a delayed sympathetic response to stress. Emotion dysregulation must be considered as a treatment target in medical settings.